Enhancing Writing Skills for ESP Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In the context of English for Specific Purposes (ESP), writing skills are crucial for students aiming to succeed in academic, professional, and vocational environments where domain-specific communication is essential. This article examines strategies for improving writing skills in ESP students, focusing on the integration of content-based instruction, task-based learning, and authentic materials. It discusses the unique challenges ESP students face, such as mastering technical vocabulary, adhering to discipline-specific writing conventions, and maintaining coherence and accuracy. Drawing from pedagogical theory and practical classroom applications, the article proposes a framework for fostering writing competence through contextualized practice and feedback. It emphasizes the need for collaborative learning, digital tools, and tailored assessment to build student confidence and autonomy in writing. The study concludes by advocating for a learner-centered, interdisciplinary approach that aligns language instruction with the specific needs of ESP learners.